(untitled) (Research, Society and Development, 2020)
The present study is a systematic review with the objective of characterizing the main findings in the literature, which report the action of exogenous melatonin in the digestive system of mice that suffered early weaning. The bibliographic research was carried out in PubMed, VHL and SCIELO using the following key words: melatonin, stress and digestive tract. A total of 118 articles were found in the 3 databases analyzed. However, after applying the inclusion/exclusion criteria, only 1 article left. The paper found addresses the action of melatonin in the small intestine of mice that were weaned early. Collectively, melatonin supplementation improves body weight gain and intestinal morphology, while exerting little effect on cell proliferation and apoptosis, as well as on goblet cells and Paneth cells in the ileum of weaning mice.